PHILOSOPHICAL STUDY ON AKE SANTOSA MYTH IN TERNATE COMMUNITY LIFE - Jerry Dounald R; Rika Nugraha (Universitas Kuningan, 2019)
Myth is a form of education about the essence of morality and ways of life in society. Myth is not just a fairy tale without the essence of the message / philosophy in it, but the myth is the most effective way of delivering teachings and guidance about the ultimate truth. With this research it can become a place for scientific studies in understanding philosophies for the user community or for readers of the research. In its development, the people of North Maluku saw the myth of Ake Santosa only as a story / saga of the past in the name of culture. But there are also those who instill the myth of Ake Santosa as a truth which in fact actually dominates the system of thinking and forming the characteristics of the user community, especially the indigenous people in Ternate. So that the formation of dualism of views, this is feared to change the values of the message / philosophy which is the teachings and guidance for the community. So we need a scientific study, which is able to become a form of method in seeing or dissecting the philosophical meaning of a myth that exists in society. The application of the theory of transfiguration began with literature and literature studies related to the myth of Ake Santosa in Ternate society in North Maluku and became primary data. Then developed through a visual study approach. Furthermore, this final data is then analyzed and transferred into the form of visual objects that give rise to other meanings of the myth itself.